2003
DOI: 10.1176/appi.ajp.160.3.522
|View full text |Cite
|
Sign up to set email alerts
|

Differential Brain Metabolic Predictors of Response to Paroxetine in Obsessive-Compulsive Disorder Versus Major Depression

Abstract: These findings suggest that, although both OCD and major depressive disorder respond to SRIs, the two syndromes have different neurobiological substrates for response. Elevated activity in the right caudate may be a marker of responsiveness to antiobsessional treatment, while lower right amygdala activity and higher midline prefrontal activity may be required for response of depressive symptoms to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
141
3
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(165 citation statements)
references
References 82 publications
17
141
3
4
Order By: Relevance
“…29 The brain region with the greatest prospect of pretreatment prediction is the rostral ACC. 68 Metabolic and electrophysiological activity changes in depression are linked in this particular part of the brain. 10 Although the rostral ACC is anatomically connected to the subgenual ACC, these regions are cytoarchitecturally distinct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The brain region with the greatest prospect of pretreatment prediction is the rostral ACC. 68 Metabolic and electrophysiological activity changes in depression are linked in this particular part of the brain. 10 Although the rostral ACC is anatomically connected to the subgenual ACC, these regions are cytoarchitecturally distinct.…”
Section: Discussionmentioning
confidence: 99%
“…Higher than normal activity in the rostral anterior cingulate cortex (ACC) has been shown to predict response to antidepressant medication in patients with major depression. 69 High theta power in the rostral ACC has also been found to predict response in a similar population. 10 This same group found that metabolism and theta activity are linked in this region.…”
mentioning
confidence: 94%
“…Although it has been suggested that the serotonin neurotransmitter system is asymmetrically distributed in the brain (Mandell and Knapp, 1979;Tucker and Williamson, 1984), the findings of postmortem studies have been inconsistent (Arato et al, 1991a;Arora and Meltzer, 1991). Neuroimaging studies have provided evidence that individual differences among depressed patients in regional brain activity are related to subsequent response to an SSRI or other antidepressants (Buchsbaum et al, 1997;Mayberg et al, 1997;Brody et al, 1999;Hoehn-Saric et al, 2001;Saxena et al, 2003;Davidson et al, 2003). Relatively greater activity of the left rectal gyrus (Buchsbaum et al, 1997), anterior cingulate (Davidson et al, 2003), or prefrontal regions (Hoehn-Saric et al, 2001) was reported to be predictive of favorable response to antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, growing evidence that individual differences among depressed patients on genetic (Zanardi et al, 2001), biochemical (Figueras et al, 1999), neuroimaging (Buchsbaum et al, 1997;Mayberg et al, 1997;Brody et al, 1999;Saxena et al, 2003;Davidson et al, 2003), electrophysiologic (Bruder et al, 2001;Cook and Leuchter, 2001;Pizzagalli et al 2001;Kalayam and Alexopoulos, 2003;Mulert et al, 2002), and neurocognitive (Dunkin et al, 2000) measures are associated with therapeutic response to an SSRI or other antidepressants.…”
Section: Introductionmentioning
confidence: 99%
“…84,85 The altered metabolic state in the brain regions examined during depression and antidepressant treatments has been demonstrated by 18-fluorodeoxyglucose PET studies. 86,87 GPD3 was found to be transcriptionally regulated in relation to changes in neuronal activity and antidepressant drug treatment. 88 Enhanced expression of GPD3 might reflect increased metabolic requirements and contribute to a higher Na/K ATPase activity that can accelerate the rate of neuronal repolarization.…”
Section: Number Of Transcripts Affected By Single and Multiple Treatmmentioning
confidence: 99%